EXPERIMENTAL INVESTIGATION OF THE EFFECT OF DISSOLUTION ON SANDSTONE PERMEABILITY, POROSITY, AND REACTIVE SURFACE AREA - Jove Colon C.F.; Oelkers E.H.; Schott J. (My University, 2004)
The temporal permeability, porosity, and reactive surface area evolution during dissolution of nonfractured/clay-free Fontainebleau sandstone cores was measured using a flow through percolation reactor. Four core dissolution experiments, each of ∼1000 h duration, were performed on sandstone cores having initial porosities ranging from 5.1 to 16.6%. All experiments were performed at 80°C and at far from equilibrium conditions using a 0.1 M NaOH input solution with a calculated in situ pH of 11.4. Permeability evolution was determined using Darcy’s law together with in situ measured differential pressures. Reactive surface area and porosity evolution were quantified from the mass of Si leaving the core during the experiments. The 5.1 and 8.9% initial porosity sandstone cores experienced porosity increases of 1.2 and 1.4 percent, respectively, during the experiments. These cores experienced a corresponding permeability increase from 0.27 to 0.74 mD and 0.57 to 0.87 mD, respectively. In contrast, the 10.6 and 16.6% initial porosity sandstone cores had permeabilities that were essentially constant during the dissolution experiments despite porosity increases of 6.3 and 2.5%, respectively. Only the 5.1% initial porosity core experienced a permeability evolution roughly consistent with a cubic law dependence on porosity. Reactive surface areas increased during the experiments for all cores; those for the 5.1, 10.6, and 16.6% initial porosity cores increased by 21±6% for each percent porosity increase. The reactive surface area of the 8.9% initial porosity core, however, increased by 148% for each percent porosity increase. These results suggest that dissolution of the 8.9% initial porosity core opened a substantial number of isolated pores, exposing new quartz grain surfaces to dissolution.